Pilot study : Investigating the chemical composition of illegal drugs and the associated prevalence of the different drug types in the Bellville and Athlone police districts in the Western Cape, South Africa - Westraat, Hendrik (Division of Forensic Medicine and Toxicology, 2016)
Very little chemical information is known about substances being abused in South-Africa. This can be attributed to the fact that possession of drugs constitutes a criminal offence. Not much research is done, and with the exception of self-reported, rehabilitation institution data, from the South African Community Epidemiology Network on Drug Use (SACENDU) and the South African Police drug related arrest data, no other data on drugs and drug use, is publically available. Drugs are being manufactured from legal and illegal chemicals in clandestine laboratories, not complying with any health, safety or quality standards causing a serious health risk in communities. The strategy for the fight against drug abuse in South Africa, the National Drug Master Plan 2013-2017 (NDMP), is compiled by the Central Drug Authority (CDA). Without proper research, data to base decisions and strategies on and proper measuring of achievements, the implementation of the plan suffers as a consequence. The Forensic Science Laboratory (FSL) of the South African Police Service (SAPS), is responsible for the chemical testing of substances, suspected of being illegal drugs, for identification purposes. This supports the prosecuting of suspects during criminal procedures. With the active ingredient known, the use of street names e.g. Tik, Choef or Speed (all referring to methamphetamine) can be abandoned and confusion and misconceptions eliminated. This pilot study investigates the arrest data, in combination with the charge laid against the arrestee and the chemically identified active ingredient in each case. Arrest data revealed a 400% increase in drug related arrests over the last 10 years, while the NDMP requires a 10% decrease. It further highlights the fact that the measurement of success (number of arrests) in the SAPS, resulted in a focus on arresting persons in possession of drugs. The dealers and manufacturers were not adequately addressed and prevention, through chemical monitoring, suffered as a result. This study also clearly revealed that international trends are not a definite indication of the extent and type of drug abuse in South African Communities. The study further attempts to contribute, and to better describe the situation of drugs and drug abuse in communities. This in turn, will provide data to develop evidence based strategies, designed to meet the defined needs of communities, one of the aspects highlighted by the minister in the NDMP, namely an intervention based on reality and local statistics. It is therefore clear that a scientific understanding of the composition of abused substances can direct treatment, policy, prevention measures and provide intelligence to combat drug abuse and illegal drug manufacturing in South Africa.